Menganalisis kemampuan pemecahan masalah matematis pada siswa kelas IX SMPN 3 cimahi dalam menyelesaikan soal statistika - Fatah Taufik M; Anik Yuliani; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The purpose of this study is to describe the ability to solve math problems in class IX junior high school students in solving problems on statistics material. The research method used is a descriptive qualitative method. The research subjects for this study were class IX students at SMPN 3 Cimahi consisting of 35 students. The data collection technique used is to test the instrument of mathematical problem solving ability test questions in the form of a written test consisting of 4 essay questions. Based on the results of the analysis, it was found that students' mathematical problem-solving abilities could be said to be still low. This can be seen from the students who get low criterion ratings on two indicators, namely indicators that identify the adequacy of data to solve problems which obtain a proportion of 37.86% and indicators for making a mathematical model of a problem and solving it which obtains a proportion of 34.29%